The use of home brew in Pacific Islands countries and territories. Issue 1 (2nd January 2018) - Nosa, Vili; Duffy, Shavonne; Singh, Debbie; Lavelio, Save; Amber, Uma; Homasi-Paelate, Avanoa; Alfred, Julia
ABSTRACT: This review examines what is known about the production and use of home brew in the Pacific Islands countries and territories. Data collection involved interviews of 78 men and women from the Marshall Islands, Papua New Guinea, Toga, and Tuvalu. The interviews were conducted in 2013 by local interviewers. The questions fell into four key areas: people's history of home-brew consumption, the reasons for home-brew use, the effects of home brew, and people's perceptions about home brew. An open ethnographic approach revealed that males are the main consumers of home brew, that home brew is consumed in private venues by those with low socioeconomic status, and that there are positive and negative outcomes associated with the use of home brew. Finally, policy implications of the findings are included in this article.